Le langage minéral du territoire d'Elmet et la pensée du devenir dans Remains of Elmet de Ted Hughes - Sophie Elzière (Caliban: French Journal of English Studies)
The weather-beaten landscapes of the Calder Valley which are conjured up in Remains of Elmet, a collection of poems by Ted Hughes and photographs by Fay Godwin, convey a sense of the frailty and pettiness of human achievements and of the relentless powers of the natural world. Hughes’s childhood region, tamed by religious custom, devastated by centuries of industrial exploitation, and further burdened by the cost of wartime, is a bleak poetic wasteland. But as nature reclaims its rights and reveals its countless and most hidden riches, it also teaches man his necessary adaptation to its rhythm and shows him new territories to explore. Hughes’s stark poetic voice, one which is still able to resonate in the middle of the deserted moors, as the rain falls and the wind howls, has literally become mineral. It is the voice of the "cantor of rock," whose wild song, working as a Deleuzian ritournelle, opens the horizons of men’s lives and deaths to unforeseen meanings.